The Meaning of the Word "Nazara" in the Qur'an (Semantic Study Analysis of Toshihiko Izutsu) - Adam, Muhammad; Nugroho, Kharis (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
In the study of the Qur'an about the discussion of Synonyms and antonyms is an important study carried out in the method of interpretation. The problem of Ta'arud (outwardly the text of one verse of the Qur'an seems very contrary to the text of the other verse) many mufassir who criticize the synonymity of words in the Qur'an because this synonymity comes not only from the perspective of language but also theology. One of the alleged words is taraduf (containing) synonymity in the Qur'an about the word Nazara. which makes the author interested in this discussion to find out the basic meaning and relational meaning of the word Nazara and the antonymity of the word The word Nazara means to see / pay attention and there are several words that almost have meanings related to each other with the word nazara namely Ra'a and basara also have the meaning of seeing. However, there are some differences in the meaning, namely Naẓara means seeing with the eyes of the head or with the eyes of the heart, namely thinking. There is also a definition as lafaz Naẓara which is seeing or paying attention to an object repeatedly. Baṣara is defined as seeing the ins and outs of objects in a more specific sensory way. And this lafaz is also often mentioned to interpret the sense of sight. And Ra'a is meant to see an object where the object has been known before the process of seeing and lafadz Ra'a also has the meaning of arguing on something. This research uses the library review method with references to journals and theses in previous research.